Nailing vs. plating in comminuted proximal ulna fractures – a biomechanical analysis - Hopf, Johannes Christof (BMC Musculoskelet Disord, 2020)
BACKGROUND: Comminuted proximal ulna fractures are severe injuries with a high degree of instability. These injuries require surgical treatment, usually angular stable plating or double plating is performed. Nailing of proximal ulna fracture is described but not performed regularly. The aim of this study was to compare a newly developed, locked proximal ulna nail with an angular stable plate in an unstable fracture of the proximal ulna. We hypothesize, that locked nailing of the proximal ulna will provide non-inferior stability compared to locked plating. METHODS: A defect fracture distal to the coronoid was simulated in 20 sawbones. After nailing or plate osteosynthesis the constructs were tested in a servo-pneumatic testing machine under physiological joint motion (0°-90°) and cyclic loading (30 N – 300 N). Intercyclic osteotomy gap motion and plastic deformation of the constructs were analyzed using micromotion video-analysis. RESULTS: The locked nail showed lower osteotomy gap motion (0.50 ± 0.15 mm) compared to the angular stable plate (1.57 ± 0.37 mm, p < 0.001). At the anterior cortex the plastic deformation of the constructs was significantly lower for the locked nail (0.09 ± 0.17 mm vs. 0.39 ± 0.27 mm, p = 0.003). No statistically significant differences were observed at the posterior cortex for both parameters. CONCLUSIONS: Nail osteosynthesis in comminuted proximal ulna fractures shows lower osteotomy gap motion and lower amount of plastic deformation compared to locking plate osteosynthesis under laboratory conditions.